Aging of polymeric materials by stray‐field NMR relaxometry with the NMR‐MOUSE. (26th April 2019) - Blümich, Bernhard
Abstract: The sensitivity of NMR relaxation to molecular motion is explored to study the aging of polymer materials and paint binder in master paintings. Polymeric materials are formulated from macromolecules with a distribution of molecular weights and low molecular weight additives. Their physical and chemical properties change with time due to exposure to temperature, mechanical stress, and solvents. These conditions lead to physical and chemical aging, which can proceed naturally over longer times or accelerated under artificial conditions in shorter times. Either procedure bears a particular signature on the molecular mobility, which can be probed nondestructively by the NMR relaxation times T 1 and T 2 . Natural aging and accelerated temperature‐ and solvent‐induced aging are summarized for synthetic polymer materials and compared to aging of binders in the paint layers of paintings aged naturally over hundreds of years and aged artificially by solvent‐cleaning procedures during restoration or at elevated temperature during forgery.